FINANCIAL SUPPORT OF HIGHER EDUCATION INSTITUTIONS IN UKRAINE - Сидор, Галина Вікторівна; Кулик, Тетяна Павлівна; Савчин , Любов Миколаївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Today, one of the most important issues is the issue of financial support for higher education institutions in Ukraine, which is considered by the world economic community. The scientific elaboration of the issue of higher education institutions financial support acquires special relevance in the context of finding ways to modernize and reform it. The purpose of the study is to carry out reforms in the field of higher education, which requires the formation of approaches to build an effective and scientifically sound mechanism for their financial support in Ukraine. To achieve this goal, the article uses general and special research methods, in particular: general scientific and special research methods – to ensure the achievement of this goal; abstract-logical and dialectical methods of analysis – to substantiate theoretical positions and conclusions. It is determined that only with proper financial support of higher education, effective combination of financial and educational policy of the state, the progressive development can be possible. It has been proven that the indicators used by the Ministry of Education to calculate the distribution of financial security give universities a clear idea of ​​the direction in which they should focus their activities in order to improve their position. The need to introduce an electronic system for monitoring the employment of higher education institutions graduates, which will stimulate universities to take into account the needs of the labor market, improve the quality of education and promote the employment of their students. We emphasise improving the formula for the distribution of financial support for higher education institutions at the expense of the employment rate. In the course of the research it was revealed that the sphere of higher education institutions activity cannot develop without proper financial support and requires constant investments. The criteria for calculating the amount of financial support for higher education institutions, proposed by the Ministry of Education, are described. Emphasis is placed on the need to introduce an electronic system for monitoring the employment of higher education institutions graduates. The importance of financial autonomy of higher educational institutions is described. It is determined to expand the grant funding for student education. It is proposed to strengthen the state financial control over the effective use of higher education institutions of budget funds in terms of improving the quality of education and effective functioning. The obtained results of the research in the form of proposals and recommendations can be used by our state during the formation of strategic vectors of the educational space development in the Ukrainian global environment.